Assessing the association of single nucleotide polymorphisms in thyroglobulin gene with age of puberty in bulls - Fernandez, María Elena (2014)
Puberty is a stage of sexual development determined by the interaction of many loci and environmental factors. Identification of genes contributing to genetic variation in this character can assist with selection for early pubertal bulls, improving genetic progress in livestock breeding. Thyroid hormones play an important role in sexual development and spermatogenic function. The objective of this study was to evaluate the association between single nucleotide polymorphisms (SNPs) located in thyroglobulin(TG) gene with age of puberty in Angus bulls. Four SNPs were genotyped in 273 animals using SEQUENOM technology and the association between markers and puberty age was analyzed. Results showed a significant association (P < 0.05) between these markers and puberty age estimated at a sperm concentration of 50 million and a progressive motility of 10%. This is the first report of an association of TG polymorphisms with age of puberty in bulls, and results suggest the importance of thyroidal regulation in bovine sexual development and arrival to puberty.